2012
DOI: 10.1128/jvi.01975-12
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Herpes Simplex Virus 1 U L 49 Gene Results in mRNA and Protein Translation Defects That Are Complemented by Secondary Mutations in U L 41

Abstract: ؊ protein synthesis defect, and the rescue by secondary mutations in vhs, occurred at the mRNA and/or translational levels, quantitative reverse transcriptase PCR (qRT-PCR) and polysome analyses were performed. We found that the absence of VP22 caused a small decrease in mRNA levels as well as a defect in polysome assembly that was independent of mRNA abundance. Both defects were complemented by the secondary mutations in vhs, indicating functional interplay between VP22 and vhs in both accumulation and transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 44 publications
9
48
0
Order By: Relevance
“…Additionally, a true revertant (the ⌬VP22Rev strain) was generated to control for any mutations that may have arisen during the recombination process. Previous studies have shown that viruses lacking VP22 replicate poorly and produce small plaques because unregulated VHS leads to altered protein expression (36,37), and this was true for the mutant reported here (data not shown). However, although decreases in both gE and VP16 packaging were observed, the absence of VP22 did not affect the expression or packaging of UL16 (Fig.…”
Section: Ultrastructural Characterization Of Ul16-null Mutantssupporting
confidence: 61%
See 1 more Smart Citation
“…Additionally, a true revertant (the ⌬VP22Rev strain) was generated to control for any mutations that may have arisen during the recombination process. Previous studies have shown that viruses lacking VP22 replicate poorly and produce small plaques because unregulated VHS leads to altered protein expression (36,37), and this was true for the mutant reported here (data not shown). However, although decreases in both gE and VP16 packaging were observed, the absence of VP22 did not affect the expression or packaging of UL16 (Fig.…”
Section: Ultrastructural Characterization Of Ul16-null Mutantssupporting
confidence: 61%
“…VP22 is a phosphorylated protein that is known to interact within a network that includes gE, gD, VP16, ICP0, and gM (8,9,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). It also binds to and negatively regulates "virion host shutoff" (VHS) protein, and thus, mutants that lack VP22 have defects in virus production and exhibit reduced protein synthesis (36,37). Because no evidence to link the VP22 and UL16 interaction networks has been reported, we investigated the possibility that these two proteins interact.…”
mentioning
confidence: 99%
“…This led the authors to conclude that VHS is lethal for the virus in the absence of VP22. Other studies on a BAC-recovered ⌬22 virus have also identified a spontaneous secondary frameshift mutation resulting in a truncated VHS (12,13).…”
mentioning
confidence: 99%
“…First, at least 23 different viral tegument proteins may be present in mature extracellular virions (8). Second, the tegument is involved in many facets of the viral life cycle, including the migration of capsids on microtubules (9)(10)(11)(12)(13)(14), the anchorage of the capsids to nuclear pores (15)(16)(17)(18)(19)(20), the transactivation of viral genes (21), the modulation of host protein expression (22,23), viral latency (24), and the regulation of the immune response (13,(25)(26)(27). Finally, many tegument proteins also interact with each other and/or with viral glycoproteins and accumulate at the trans-Golgi network (TGN), where they altogether delineate the likely final envelopment site (4,5,28).…”
mentioning
confidence: 99%